A study to identify the prevalence of vulvovaginal candidiasis in second trimester - Kruthipati, Rashmi; Chethan, Radhika; Shiva, Anitha Gabbalkaje; Suresh, Sukanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Vaginal candidial infections are due to excessive growth of Candida. These are normally present in the vagina in small numbers. Vaginal infections are typically caused by the yeast species Candida albicans. It is found that candidial infection increases the risk of preterm labour. Aims and objectives of the study were to determine the prevalence of vulvovaginal candidiasis and influence of maternal age, parity and weeks of 2nd trimester on its occurrence among pregnant women in 2nd trimester, attending the antenatal clinic in our hospital. Methods: A prospective study conducted in BMCRI for a period of 3 months (October 2019-December 2019) on patients in second trimester. Consent of patients taken. High vaginal swabs were collected from the pregnant patients in second trimester and sent for culture. Candida positive cases were noted and results were analysed. Results: A total of 100 high vaginal swabs were collected and reported in our study. Among them 54 swabs were positive for Candida growth (54%) and 46 swabs were negative for growth (46%). Culture positive patients’ clinical details were analysed and tabulated. Conclusions: Our study concluded that candidiasis is more prevalent in pregnant women but there was no statistical significance in occurrence of vaginal candidiasis among various age groups, parity or trimester. Hence it is better to screen all the patients in I early II trimester in order to find out and treat positive cases early to prevent preterm births attributed to vaginal candidiasis.